2012
DOI: 10.1037/a0028995
|View full text |Cite
|
Sign up to set email alerts
|

Taking it to the classroom: Number board games as a small group learning activity.

Abstract: We examined whether a theoretically based number board game could be translated into a practical classroom activity that improves Head Start children's numerical knowledge. Playing the number board game as a small group leaming activity promoted low-income children's number line estimation, magnitude comparison, numeral identification, and counting. Improvements were also found when a paraprofessional from the children's classroom played the game with the children. Observations of the game-playing sessions rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 55 publications
4
105
2
11
Order By: Relevance
“…These results add additional support to the growing literature of play-based mathematics interventions for lowincome and struggling early learners (Laski & Siegler, 2014;Ramani, Siegler, & Hitti, 2012;Räsänen, Salminen, Wilson, Aunio, & Dehaene, 2009;Whyte & Bull, 2008). Although many previous studies with low-income preschoolers have focused on linear number board game interventions designed to promote children's mental number line (e.g., Siegler & Ramani, 2009), a representation of their magnitude understanding, the current study suggests that numerical card games may lead to similar improvements in children's early math skills.…”
Section: Early Mathematics Gap 574supporting
confidence: 63%
“…These results add additional support to the growing literature of play-based mathematics interventions for lowincome and struggling early learners (Laski & Siegler, 2014;Ramani, Siegler, & Hitti, 2012;Räsänen, Salminen, Wilson, Aunio, & Dehaene, 2009;Whyte & Bull, 2008). Although many previous studies with low-income preschoolers have focused on linear number board game interventions designed to promote children's mental number line (e.g., Siegler & Ramani, 2009), a representation of their magnitude understanding, the current study suggests that numerical card games may lead to similar improvements in children's early math skills.…”
Section: Early Mathematics Gap 574supporting
confidence: 63%
“…For whole numbers, it has been shown that simple feedback interventions (Opfer & Siegler, 2007) and even numerical board games (Ramani & Siegler, 2008), in which children map numbers onto space, can substantially improve children's magnitude understanding. These interventions can be implemented in classrooms easily and effectively (Ramani, Siegler, & Hitti, 2012). The intervention effects are particularly strong for children from low-income households, who have fewer experiences in playing number games and have less numerical knowledge than their peers (Siegler, 2009).…”
Section: Instructional Implicationsmentioning
confidence: 99%
“…According to the National Mathematics Advisory Panel [24], board games are "particularly effective in improving low-income preschoolers' numerical knowledge and reducing discrepancies in the numerical knowledge that children from low-and middle-income homes bring to school." They are engaging and effective for classroom context [18]. Espiral Mágico is a board game that has been designed to practice word problems using the curricular content selected by the teacher.…”
Section: Methodsmentioning
confidence: 99%